Joyful noise : poems for two voices - Fleischman, Paul.; Beddows, Eric, 1951- (New York : Harper & Row, 1988)
A collection of poems describing the characteristics and activities of a variety of insects.
"A Charlotte Zolotow book."
Keywords: Insects -- Juvenile poetry; Children's poetry, American; Insects -- Poetry; American poetry; Newbery Medal